Jews and Christians in the ancient Golan heights - Ma'oz, Zvi Uri (2010)
It is commonplace among scholars that the three major groups of population - Jews, Christians and pagans - coexisted in the principal cities of Palestine. Whether this was the situation in the countryside as well is a much debated question. Ancient Golan is the best test case for this question since some ten sites are claimed to have a Jewish presence within the overwhelming Christian population. This article examines the evidence for the purported Jewish existence in these villages. Since no archaeological basis is found for this claim, it is concluded that Jews did not live among Christians in the ancient Golan Heights.
Keywords: Stadt; Archäologie; Golanhöhen